Genetic Transformation of Common Bean (Phaseolus vulgaris L.) with the Gus Color Marker, the Bar Herbicide Resistance, and the Barley (Hordeum vulgare) HVA1 Drought Tolerance Genes - Kingdom Kwapata; Thang Nguyen; Mariam Sticklen (International Journal of Agronomy)
Five common bean (Phaseolus vulgaris L.) varieties including “Condor,” “Matterhorn,” “Sedona,” “Olathe,” and “Montcalm” were genetically transformed via the Biolistic bombardment of the apical shoot meristem primordium. Transgenes included gus color marker which visually confirmed transgenic events, the bar herbicide resistance selectable marker used for in vitro selection of transgenic cultures and which confirmed Liberty herbicide resistant plants, and the barley (Hordeum vulgare) late embryogenesis abundant protein (HVA1) which conferred drought tolerance with a corresponding increase in root length of transgenic plants. Research presented here might assist in production of better P. vulgaris germplasm.